Pre-Clinical Model to Study Recurrent Venous Thrombosis in the Inferior Vena Cava - Andraska, Elizabeth A.; Luke, Catherine E.; Elfline, Megan A.; Henke, Samuel P.; Madapoosi, Siddharth S.; Metz, Allan K.; Hoinville, Megan E.; Wakefield, Thomas W.; Henke, Peter K.; Diaz, Jose A. (Thrombosis and Haemostasis, 2018)
Background Patients undergoing deep vein thrombosis (VT) have over 30% recurrence, directly increasing their risk of post-thrombotic syndrome. Current murine models of inferior vena cava (IVC) VT model host one thrombosis event.Objective We aimed to develop a murine model to study IVC recurrent VT in mice.Materials and Methods An initial VT was induced using the electrolytic IVC model (EIM) with constant blood flow. This approach takes advantage of the restored vein lumen 21 days after a single VT event in the EIM demonstrated by ultrasound. We then induced a second VT 21 days later, using either EIM or an IVC ligation model for comparison. The control groups were a sham surgery and, 21 days later, either EIM or IVC ligation. IVC wall and thrombus were harvested 2 days after the second insult and analysed for IVC and thrombus size, gene expression of fibrotic markers, histology for collagen and Western blot for citrullinated histone 3 (Cit-H3) and fibrin.Results Ultrasound confirmed the first VT and its progressive resolution with an anatomical channel allowing room for the second thrombus by day 21. As compared with a primary VT, recurrent VT has heavier walls with significant up-regulation of transforming growth factor-β (TGF-β), elastin, interleukin (IL)-6, matrix metallopeptidase 9 (MMP9), MMP2 and a thrombus with high citrullinated histone-3 and fibrin content.Conclusion Experimental recurrent thrombi are structurally and compositionally different from the primary VT, with a greater pro-fibrotic remodelling vein wall profile. This work provides a VT recurrence IVC model that will help to improve the current understanding of the biological mechanisms and directed treatment of recurrent VT.
Keywords: animal model; disease models; recurrence; venous thrombosis; venous thromboembolism